Framing Conflict: American Media’s Framing of the Israel-Hamas War - Park, Chang Sup; Oliullah, Md (International Journal of Mass Communication, 2025)
A content analysis of 335 news articles from The New York Times, The Washington Post, CNN, and Fox News published between October 2023 and March 2024 reveals that Fox News predominantly employs the ‘security threat’ frame, portraying Israel’s actions as necessary defenses, while The New York Times and CNN emphasize ‘humanitarian crisis’ and ‘moral responsibility’ frames, highlighting impacts on Palestinian civilians and ethical concerns. The Washington Post takes a more balanced but critical approach toward the war. We also interviewed 10 journalists from the four media channels, and they confirmed and elaborated on what we found in the content analysis. These outcomes demonstrate that in the coverage of an international conflict media framing may take a bidirectional nature, where media influence public opinion while simultaneously adapting to audience perceptions.